2005
DOI: 10.1089/jir.2005.25.321
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interaction Between Nuclear Coactivator CBP and the Protein Inhibitor of Activated Stat1 (PIAS1)

Abstract: cAMP response element binding protein (CREB)-binding protein (CBP) is a multifunctional transcriptional coactivator that plays important roles in gene regulation. CBP is expressed in murine embryonic orofacial tissue, where it is developmentally regulated. To identify nuclear factors associated with CBP in developing orofacial tissue, a yeast two-hybrid screen of a cDNA library derived from embryonic orofacial tissue from gestational days 11-13 mouse embryos was conducted. Using the carboxy terminal region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We expected that besides general, housekeeping proteins, shared partners in the two different libraries may point to functionally important and potentially disease-associated interaction partners of CBP/p300 mediated by ID3, mitigating the effect of known high false positive hit rates of Y2H. A total of 37 proteins were classified as potential ID3 binders, including 4 candidates that have already been described to interact with CBP or p300 (HIPK1 32 , PIAS1 33 , PAIS3 34 and TDG 35 ) (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…We expected that besides general, housekeeping proteins, shared partners in the two different libraries may point to functionally important and potentially disease-associated interaction partners of CBP/p300 mediated by ID3, mitigating the effect of known high false positive hit rates of Y2H. A total of 37 proteins were classified as potential ID3 binders, including 4 candidates that have already been described to interact with CBP or p300 (HIPK1 32 , PIAS1 33 , PAIS3 34 and TDG 35 ) (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…It is also supported by the findings that PIAS1 promotes the sumoylation of metabotropic glutamate receptor 8 (Tang et al, 2005), whereas metabotropic glutamate receptors are involved in regulating synaptic activity (Luscher and Huber, 2010). Furthermore, PIAS1 was found to interact with the CREB-binding protein (CBP) (Yin et al, 2005), whereas CBP is a transcriptional coactivator for CREB and the CREB/CBP complex is suggested to mediate the memory-enhancing effect of histone deacetylase (HDAC) inhibitors through regulation of target gene expression (Vecsey et al, 2007). Moreover, our results revealed that PIAS1 expression is also regulated by PI-3 kinase signaling through the mediation of CREB because both LY294002 and wortmannin treatments down-regulated the expression of PIAS1 accompanied by a decreased phosphorylation level of CREB.…”
Section: Discussionmentioning
confidence: 99%
“…CBP possesses histone acetyltransferase activity and dissociates histones for chromatin relaxation in the promoter region. The CBP/p300 co-activators function in concert with a variety of transcription factors including c-Myb, p53, STATs, NF-κB, PIAS1, and the IRF family (Barlev et al, 2001;Lin et al, 2000;Ma et al, 2005;Oelgeschläger et al, 1996;Yin et al, 2005;Zhong et al, 2002). Therefore, CBP acts as an important regulator for many cellular processes.…”
Section: Discussionmentioning
confidence: 99%